2008
DOI: 10.1073/pnas.0710181105
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor-1 receptor involvement in behavioral neuroadaptation to ethanol: A urocortin 1 -independent mechanism

Abstract: A common expression of neuroadaptations induced by repeated exposure to addictive drugs is a persistent sensitized behavioral response to their stimulant properties. Neuroplasticity underlying drug-induced sensitization has been proposed to explain compulsive drug pursuit and consumption characteristic of addiction. The hypothalamic-pituitary-adrenal (HPA) axis-activating neuropeptide, corticotropin-releasing factor (CRF), may be the keystone in drug-induced neuroadaptation. Corticosterone-activated glucocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 74 publications
(104 reference statements)
4
86
0
1
Order By: Relevance
“…Importantly, Wulsin and co-workers also found no effect of mifepristone on the stress-induced response in the paraventricular nucleus of the hypothalamus, which points to extrahypothalamic site of action for its anti-stress and anti-depressant effects. CORT binding has been shown to negatively regulate HPA axis function in the hypothalamus, while it has stimulatory effects in extrahypothalamic regions, including the CeA (Makino et al, 1994;Pastor et al, 2008). Furthermore, inactivation of the CeA, but not the BLA, has been shown to block footshock-induced reinstatement of cocaine-seeking (McFarland et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Wulsin and co-workers also found no effect of mifepristone on the stress-induced response in the paraventricular nucleus of the hypothalamus, which points to extrahypothalamic site of action for its anti-stress and anti-depressant effects. CORT binding has been shown to negatively regulate HPA axis function in the hypothalamus, while it has stimulatory effects in extrahypothalamic regions, including the CeA (Makino et al, 1994;Pastor et al, 2008). Furthermore, inactivation of the CeA, but not the BLA, has been shown to block footshock-induced reinstatement of cocaine-seeking (McFarland et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral sensitization induced by ethanol (EtOH) has been largely studied in mice (Masur and Boerngen, 1980;Phillips et al, 1997;Broadbent et al, 2003;Pastor et al, 2008), but also demonstrated in rats (Correa et al, 2003) and humans (Newlin and Thomson, 1999). However, the neurobiological determinants of EtOH sensitization remain to be entirely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Results pertaining to the participation of dopamine (Broadbent et al, 1995;Palmer et al, 2003), opioid (Pastor and Aragon, 2006;Abrahao et al, 2008), ␥-aminobutyric acid (Chester and Cunningham, 1999;Meyer et al, 2005), and glutamate (Broadbent et al, 2003;Meyer and Phillips, 2007) systems in ethanol sensitization have not provided consistent support. It is noteworthy that manipulation of hypothalamic-pituitary-adrenal (HPA)-axis components, such as corticotropin-releasing factor (CRF) or glucocorticoids, has been shown to critically modulate EtOH-induced behavioral sensitization (Roberts et al, 1995;Phillips et al, 1997;Fee et al, 2007;Pastor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations